AN EXAMINATION OF AICPA RESEARCH STUDY NO. 5–STANDARDS FOR POOLING. - Sapienza, S. R. (The Accounting Review, 1964)
Abstract The article informs that the purpose of this article is to discuss the viewpoints expressed in, "A Critical Study of Accounting for Business Combinations," AICPA Study No. 5, by Arthur R. Wyatt. This review will concentrate on the recommendations rather than the basic text. The role adopted will be, in a sense, that of "devil's advocate." Using Wyatt's criteria, most business combinations would fall under his recommendation 1 and therefore be classified as purchases. Stress is put on the independence of the contracting or combining parties. Thus, if the groups about to combine deal at arm's length and independently, the proposed combination will be a purchase unless the constituents are roughly the same size or were "formerly related entities." While two parties to a combination might be viewed as independent before the combination, they do not want to retain their independence after the transaction.